213k views
3 votes
Please help me to do this problem of system by sustitution.

Please help me to do this problem of system by sustitution.-example-1
User Haouarin
by
4.7k points

1 Answer

3 votes

\begin{gathered} 6x+2y=2---(1) \\ -6x-2y=8---(2) \\ \text{From equation (1), let 6x = 2 - 2y} \\ \text{Substitute for the value of 6x into equation (2)} \\ -6x-2y=8 \\ -(2-2y)-2y=8 \\ -2+2y-2y=8 \\ -2=8 \end{gathered}

Please note that this equation cannot be solved by substitution. The result shows that it has no solution, because -2 does not equal to 8.

User Seer
by
4.8k points